OCULAR ADVERSE EVENTS ASSOCIATED WITH MEK INHIBITORS. Issue 8 (August 2019) - Méndez-Martínez, Silvia; Calvo, Pilar; Ruiz-Moreno, Oscar; Pardiñas Barón, Nieves; Leciñena Bueno, Jesús; Gil Ruiz, María del Rocío; Pablo, Luis
Abstract : Purpose: Mitogen-activates protein kinase (MAPK) inhibitors, particularly MEK inhibitors, have shifted the treatment paradigm for metastatic BRAF-mutant cutaneous melanoma; however, oncologists, ophthalmologists, and patients have noticed different toxicities of variable importance. This review aims to provide an update of the ocular adverse events (OAEs), especially retinal toxicity, associated with the use of MEK inhibitors. Methods: We conducted a scientific literature search using the PubMed database up to July 2018 with the terms "MEK inhibitors" with a "review" filter and "MEK inhibitors" with a "clinical trials" filter. Phase I–III experimental studies and reviews were selected. Current principles and techniques for diagnosing and managing MEK inhibitor retinopathy and other OAEs are discussed. Results: In patients treated with MEK inhibitors, including asymptomatic patients, OAEs occur with an incidence of up to 90%. Mild to severe ophthalmic toxicities are described, including visual disturbances, a 2-line decrease in Snellen visual acuity, dry eye symptoms, ocular adnexal abnormalities, visual field defects, panuveitis, and retinal toxicities, such as different degrees of MEK-associated retinopathy, vascular injury, and retinal vein occlusion. Conclusion: MEK inhibitors can lead to different degrees of retinal, uveal, and adnexal OAE, causing visual disturbances or discomfort. One of the most relevant OAE of MEK therapy is MEK inhibitor–associated retinopathy (MEKAR), which is usually mild, self-limited, and may subside after continuous use of the drug for weeks or months, or discontinuation, thereby restoring the normal visual function of the retina, with some exceptions. Ocular adverse events are often associated with other systemic adverse effects that can modify the dosage of treatment, so the communication with the oncologist is fundamental. Abstract : Mitogen-activated protein kinase inhibitors are anticancer drugs used for BRAF-mutant metastatic tumors. Although clinical trials demonstrated their safety, several ocular adverse events were also described, including visual disturbances, dry eye symptoms, ocular adnexal abnormalities, and retinal disturbances. This review reports the main ocular adverse events described in the literature.